Integral options in models with jumps - Pavel V. Gapeev (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
We present an explicit solution to the formulated in [17] optimal stopping problem for a geometric compound Poisson process with exponential jumps. The method of proof is based on reducing the initial problem to an integro-differential free-boundary problem where the smooth fit may break down and then be replaced by the continuous fit. The result can be interpreted as pricing perpetual integral options in a model with jumps.
Keywords: 330